PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN PENDEKATAN ROGERS PADA SISWA SEKOLAH MENENGAH ATAS - Sape, Herwandi (Jurnal Penalaran dan Riset Matematika, 2024)
This research is a type of Pre-Experimental research. This study aims to determine the effectiveness of mathematics learning through the application of Rogers' approach in PGRI Tamalate 2 Makassar high school students. The research design used was One Group Pretest-Posttest Design. The instruments used in this study were learning outcome tests, student activity observation sheets, and student response questionnaires. The results in this study are the average mathematics learning outcomes of students after applying the Rogers Approach is 81.78 with a standard deviation of 9.24 and generally included in the high category. This result also shows that from the total number of students can be completed classically. The average normalized gain on student learning outcomes was 0.7 so that the increase in student learning outcomes was in the high category. The average percentage frequency of student activity was 83.09%, thus student activity reached active criteria. The average student response was 87.5%, thus students were classified as giving a positive response to the application of Rogers' approach.